ANALISIS KEBERLANJUTAN USAHATANI PADI DI KABUPATEN SIAK (Studi Kasus di Gapoktan Mekar Jaya, Kecamatan Sabak Auh) - Fadhlan Zuhdi; Achmad Saiful Alim; Viona Zulfia (EnviroScienteae, 2021)
This study aims to identify the sustainability of rice farming in Siak Regency, Riau Province. The data used are primary data and the farmers farmers who have rice farming who are members of the Mekar Jaya Gapoktan as sample. Multidimensional Scaling (MDS) analysis with the Rapfish approach is used to see the sustainability status of rice farming based on five dimensions, namely ecological, economic, social, technological, and institutional dimensions. Based on the results of the study, it can be seen from the ordinance value of MDS that four dimensions are included in the indicators of being quite sustainable, namely the ecological, social, technological, and institutional dimensions. However, the economic dimension is in a less sustainable indicator where business partnerships are the lever aspect that has the greatest value on that dimension. The establishment of business partners is one solution that is expected to be able to overcome the problem of economic sustainability of rice farming in Siak Regency, thus farmers have certainty in selling farming products so that it is expected to be able to reduce the impact of uncertainty that leads to the sustainability of farming.